Introducing Bahasa Indonesia bagi Penutur Asing (BIPA): Method and challenges of teaching Indonesian as a Foreign Language (IFL) - Tira Nur Fitria (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2023)
This research describes the method and challenges in teaching Bahasa Indonesia bagi Penutur Asing (BIPA) or Indonesian as a Foreign Language (IFL) to foreign learners. Effective teaching BIPA relies on various factors, including teaching methods. BIPA teachers should consider effective teaching methods for learners’ language acquisition. Teachers can build a pleasant initial atmosphere in the BIPA class using direct methods, grammar translation, audio-linguistic, community-based learning, and communicative approaches. Several obstacles may occur while teaching BIPA. The internal aspects are the teacher, learners, teaching and learning process, media, and teaching materials. Indonesian learners’ challenges are pronunciation or spelling, limited practice time, self-confidence, student motivation or interest, age factors, personality or characteristics, and student abilities. Teachers’ challenges are related to teaching experience, low competence, and urgent needs of the teacher. The other obstacles are the availability of teaching materials in the textbooks, audio video, and additional online sources of BIPA teaching materials, time teaching, and BIPA curriculum. The external factors are inadequate educational support facilities and infrastructure, cross-cultural learning, different perspectives, students’ cultural and linguistic background, self-adaptation, heterogeneous class situations, search for cultural similarities, and students’ needs, environment, overseas administration, place of residence, weather, natural conditions, and geography of the country, even government policy. AbstrakPenelitian ini mendeskripsikan metode dan tantangan dalam pengajaran Bahasa Indonesia bagi Penutur Asing (BIPA) atau Indonesian as a Foreign Language (IFL) kepada pembelajar asing. Pengajaran BIPA yang efektif bergantung pada berbagai faktor, termasuk metode pengajaran. Guru BIPA harus mempertimbangkan metode pengajaran yang efektif untuk pemerolehan bahasa pembelajar. Guru dapat membangun suasana awal yang menyenangkan di kelas BIPA dengan menggunakan metode langsung, tata bahasa terjemahan, audio-linguistik, pembelajaran berbasis masyarakat, dan pendekatan komunikatif. Beberapa kendala dapat terjadi selama pengajaran BIPA. Aspek internal adalah guru, peserta didik, proses belajar mengajar, media, dan bahan ajar. Tantangan pembelajar bahasa Indonesia adalah dalam pengucapan atau ejaan, waktu latihan yang terbatas, kepercayaan diri, motivasi atau minat siswa, faktor usia, kepribadian atau karakteristik siswa, dan kemampuan siswa. Tantangan guru terkait dengan pengalaman mengajar, rendahnya kompetensi guru, dan kebutuhan guru yang mendesak. Kendala lainnya adalah ketersediaan bahan ajar berupa buku teks, audio video, dan tambahan sumber online bahan ajar BIPA, waktu pengajaran, dan kurikulum BIPA. Faktor eksternal adalah sarana dan prasarana penunjang pendidikan yang kurang memadai, pembelajaran lintas budaya, perbedaan perspektif, latar belakang budaya dan bahasa siswa, penyesuaian diri, situasi kelas yang heterogen, pencarian kesamaan budaya, dan kebutuhan siswa, lingkungan, administrasi luar negeri, tempat tempat tinggal, cuaca, kondisi alam, dan geografi negara, bahkan kebijakan pemerintah.Kata Kunci: Bahasa Indonesia bagi Penutur Asing; Bahasa Indonesia sebagai Bahasa Asing; BIPA; IFL; mengajar Bahasa Indonesia untuk Pembelajar Asing